2020
DOI: 10.1101/2020.07.28.225060
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Kappa Opioid Receptor Agonists on Fentanyl vs. Food Choice in Male and Female Rats: Contingent vs. Non-Contingent Administration

Abstract: RationaleStrategies are needed to decrease the abuse liability of mu opioid receptor (MOR) agonists. One strategy under consideration is to combine MOR agonists with kappa opioid receptor (KOR) agonists.ObjectivesThe effects of KOR-agonists (U50488, nalfurafine) on fentanyl-versus-food choice were compared under conditions where the KOR agonists were added to the self-administered fentanyl (contingent delivery) or administered as pretreatments (non-contingent delivery) in male and female rats. The effects of i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…A series of studies showed that acute nalfurafine dose‐dependently suppresses morphine‐induced hyperlocomotion and that repeated nalfurafine treatment not only blocks naloxone‐precipitated withdrawal syndromes after chronic morphine treatment but also reduces morphine‐induced conditioned place preference as well as oxycodone‐induced conditioned place preference and self‐administration in rodents by activating κ receptor(Kaski et al, 2019; Tsuji et al, 2000; Zamarripa, Patel, et al, 2020; Y. Zhang & Kreek, 2020). However, under a drug‐versus‐food choice procedure, non‐contingent U50488 and nalfurafine administration decreases the number of choices made during the behavioural session without altering fentanyl choice in rats (Townsend, 2021),. This suggests that κ receptor agonists may decrease operant behaviours by non‐selectively decreasing behavioural responses through impairing sensory, cognitive or motor functions (undesired effects), rather than decreasing sensitivity to the reinforcing effects of the self‐administered opioid (the desired effect).…”
Section: Potential Targets or Treatment Strategies For Opioid Use Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies showed that acute nalfurafine dose‐dependently suppresses morphine‐induced hyperlocomotion and that repeated nalfurafine treatment not only blocks naloxone‐precipitated withdrawal syndromes after chronic morphine treatment but also reduces morphine‐induced conditioned place preference as well as oxycodone‐induced conditioned place preference and self‐administration in rodents by activating κ receptor(Kaski et al, 2019; Tsuji et al, 2000; Zamarripa, Patel, et al, 2020; Y. Zhang & Kreek, 2020). However, under a drug‐versus‐food choice procedure, non‐contingent U50488 and nalfurafine administration decreases the number of choices made during the behavioural session without altering fentanyl choice in rats (Townsend, 2021),. This suggests that κ receptor agonists may decrease operant behaviours by non‐selectively decreasing behavioural responses through impairing sensory, cognitive or motor functions (undesired effects), rather than decreasing sensitivity to the reinforcing effects of the self‐administered opioid (the desired effect).…”
Section: Potential Targets or Treatment Strategies For Opioid Use Dis...mentioning
confidence: 99%
“…This suggests that κ receptor agonists may decrease operant behaviours by non‐selectively decreasing behavioural responses through impairing sensory, cognitive or motor functions (undesired effects), rather than decreasing sensitivity to the reinforcing effects of the self‐administered opioid (the desired effect). Although κ receptor agonists can function as punishers, decrease opioid self‐administration and choice when mixed and co‐administered with the abuse drug (Townsend, 2021; Zamarripa, Naylor, et al, 2020), it is unlikely that the abuse liability of the drugs of abuse can be eliminated by mixing it with another drug. Overall, this body of literature does not support the clinical utility of κ receptor agonists as potential treatment strategies for opioid use disorder.…”
Section: Potential Targets or Treatment Strategies For Opioid Use Dis...mentioning
confidence: 99%
“…The trans-3,4-dichloro-N-methyl-N-[2-(1-pyrrolidinyl)cyclohexyl]-benzeneacetamide derivative U-50,488 is a selective KOR agonist, possessing analgesic, cough suppressant, and diuretic properties. It also suppresses the psychostimulant reward through the inhibition of dopamine signaling in the addiction pathways [ 10 , 11 , 12 ], with obvious influence in decreasing amphetamine-induced psychomotor disturbances [ 13 ], in preventing cocaine [ 14 ] or nicotine-induced motor troubles [ 15 ], and in reducing the charges of morphine [ 16 ] or fentanyl [ 17 ] self-administration in rodents. Other research has evidenced the beneficial effects of U50,488 on L-dopa attenuation of motor dyskinesia in rodents and primates with experimental-induced Parkinsonian manifestations [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%